2016
DOI: 10.1177/1933719115623644
|View full text |Cite
|
Sign up to set email alerts
|

Nerve Bundles and Deep Dyspareunia in Endometriosis

Abstract: The etiology of deep dyspareunia in endometriosis is unclear. Our objective was to determine whether nerve bundle density in the cul-de-sac/uterosacrals (zone II) is associated with deep dyspareunia in women with endometriosis. We conducted a blinded retrospective immunohistochemistry study (n = 58) at a tertiary referral center (2011-2013). Patients were stringently phenotyped into a study group and 2 control groups. The study group (tender endometriosis, n = 29) consisted of patients with deep dyspareunia, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 29 publications
1
29
0
Order By: Relevance
“… 10 , 11 , 32 Tenderness of the cul-de-sac or uterosacral ligaments in endometriosis can arise from local neuroinflammation, 33 and in previous work we found that local nerve density correlates to deep dyspareunia severity in cul-de-sac or uterosacral endometriosis. 15 However, we also found that tenderness of the bladder, pelvic floor, and cervix and uterus was similarly present in women with and without endometriosis. This could account for why women with the same type and location of endometriosis can have wide variability in deep dyspareunia symptoms.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“… 10 , 11 , 32 Tenderness of the cul-de-sac or uterosacral ligaments in endometriosis can arise from local neuroinflammation, 33 and in previous work we found that local nerve density correlates to deep dyspareunia severity in cul-de-sac or uterosacral endometriosis. 15 However, we also found that tenderness of the bladder, pelvic floor, and cervix and uterus was similarly present in women with and without endometriosis. This could account for why women with the same type and location of endometriosis can have wide variability in deep dyspareunia symptoms.…”
Section: Discussionsupporting
confidence: 53%
“…The sample size of this cohort is 548. Based on data from a previous retrospective dataset, 15 for the association between pelvic floor tenderness and severity of deep dyspareunia (with power = 0.99, α = 0.05, SD = 2.57, mean difference = 1.15, and incidence of pelvic floor tenderness = 33%), a sample size of 480 would be required. 30 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Endometriosis is a well‐known and key cause of deep dyspareunia in women of reproductive age (Howard et al, ; De Sousa et al, ; William et al, ; Yong et al, ). It can be defined as the presence of ectopic endometrial tissue outside of the uterus (De Sousa et al, ; Yong et al, ).…”
Section: Pathophysiology Of Dyspareuniamentioning
confidence: 99%
“…The prevalence of endometriosis in women of reproductive age is approximately 10%, with about half of these having deep dyspareunia (Yong et al, ). One study observed an increase density of nociceptive nerve bundles in the uterosacral ligaments of women with endometriosis proposing local neurogenesis as a cause of deep dyspareunia in patients with this disorder (William et al, ). However, the severity of the dyspareunia varies among women with laparoscopic evidence of endometriosis.…”
Section: Pathophysiology Of Dyspareuniamentioning
confidence: 99%